TRiC/CCT chaperonin is required for the folding and inhibitory effect of WDTC1 on adipogenesis - Tang, Wen-Shuai; Cen, Xiang; Yao, Shan-Shan; Yin, Shu-Ting; Weng, Li; Zhao, Tong-Jin; Wang, Xu (Frontiers in Cell and Developmental Biology, 2023)
Obesity has become a global pandemic. WDTC1 is a WD40-containing protein that functions as an anti-obesity factor. WDTC1 inhibits adipogenesis by working as an adaptor of the CUL4-DDB1 E3 ligase complex. It remains unclear about how WDTC1 is regulated. Here, we show that the TRiC/CCT functions as a chaperone to facilitate the protein folding of WDTC1 and proper function in adipogenesis. Through tandem purification, we identified the molecular chaperone TRiC/CCT as WDTC1-interacting proteins. WDTC1 bound the TRiC/CCT through its ADP domain, and the TRiC/CCT recognized WDTC1 through the CCT5 subunit. Disruption of the TRiC/CCT by knocking down CCT1 or CCT5 led to misfolding and lysosomal degradation of WDTC1. Furthermore, the knockdown of CCT1 or CCT5 eliminated the inhibitory effect of WDTC1 on adipogenesis. Our studies uncovered a critical role of the TRiC/CCT in the folding of WDTC1 and expanded our knowledge on the regulation of adipogenesis.